Bioluminescent coelenterazine derivatives with imidazopyrazinone C-6 extended substitution - Nishihara, Ryo; Suzuki, Hideyuki; Hoshino, Emi; Suganuma, Sakura; Sato, Moritoshi; Saitoh, Tsuyoshi; Nishiyama, Shigeru; Iwasawa, Naoko; Citterio, Daniel; Suzuki, Koji (Chemical communications (Cambridge, England), 2015)
Three novel coelenterazine (CTZ) derivatives with extension at the C-6 position of the imidazopyrazinone structure show significant bioluminescence emission with known renilla luciferase variants, indicating a promising method to develop CTZ derivatives with superior optical properties compared to hitherto reported compounds.